Adoption of accrual accounting in local authorities of Kedah Darul Aman - Omar, Ropidah; Amran, Noor Afza; Aripin, Norhani (2005)
This study focuses on eleven municipal and district councils in Kedah Darul Aman, viewing whether local authorities adopt the accrual accounting in recording the income and expenditures and the problems faced by local authorities in adopting accrual accounting approach.The study found that only 5 of 11(45%) local authorities in Kedah Darul Aman disclosed the use of accrual accounting in their application of accounting policies in the financial statements.Furthermore, there are certain items under income and expenditure that are still reported using cash basis.The nature of the items themselves, lacking in guidelines and also lacking in number of staff with experience and accounting education are part of the problems facing the local authorities in adopting the accrual accounting.